Analisis Unsur Intrinsik Dalam Komik Lookism Karya Park Tae-Jun - Levi Al Kausar; Siti Muslimah; Ruliyani Ruliyani; Anwarsani Anwarsani; Siti Rahmawati; Nabila Salwa (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
The comic